2022
DOI: 10.1038/s44183-022-00006-2
|View full text |Cite
|
Sign up to set email alerts
|

Getting beyond yes: fast-tracking implementation of the United Nations agreement for marine biodiversity beyond national jurisdiction

Abstract: With a new international agreement on the conservation and sustainable use of marine biodiversity of areas beyond national jurisdiction (BBNJ Agreement) on the horizon, now is the time to start laying the foundation for successful implementation. This paper provides some initial reflections for supporting rapid, effective, and equitable implementation of the BBNJ Agreement in three priority areas: (1) bringing the Agreement into force; (2) establishing the institutional framework, including financial mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…In the case of ABMTs, including MPAs, in order to meet conservation requirements and still meet stakeholder interests, a multidisciplinary approach is essential to balance social and ecological factors (Ruiz-Frau et al, 2015). The multitude of research fields identified in our data indicates that the same applies to the BBNJ agreement, i.e., a successful implementation must consider a multidisciplinary approach in which international governmental cooperation, solid laws, and the exchange of scientific knowledge regarding environmental and ecological aspects are equally relevant, as previously discussed by Gjerde et al (2022).…”
Section: The Growing Interest On Promoting the Conservation Of Biodiv...supporting
confidence: 55%
“…In the case of ABMTs, including MPAs, in order to meet conservation requirements and still meet stakeholder interests, a multidisciplinary approach is essential to balance social and ecological factors (Ruiz-Frau et al, 2015). The multitude of research fields identified in our data indicates that the same applies to the BBNJ agreement, i.e., a successful implementation must consider a multidisciplinary approach in which international governmental cooperation, solid laws, and the exchange of scientific knowledge regarding environmental and ecological aspects are equally relevant, as previously discussed by Gjerde et al (2022).…”
Section: The Growing Interest On Promoting the Conservation Of Biodiv...supporting
confidence: 55%
“…27 An evaluation of the needs, in this context, will be an important first step, at national and regional levels. 28 In addition, according to Article 43(2), the transfer of marine technology "shall take place on fair and most favorable terms, including on concessional and preferential terms, and in accordance with mutually agreed terms and conditions as well as the objectives of this Agreement"; it also "shall take into account all rights over such technologies and be carried out with due regard for all legitimate interests, including, inter alia, the rights and duties of holders, suppliers and recipients of marine technology and taking into particular consideration the interests and needs of developing States for the attainment of the objectives of this Agreement". This submission to existing practices and rules in this area probably reflects the fact that a strict obligation of technology transfer might be in contradiction with international economic law and especially investment law.…”
Section: (Ii) Modalities For Transfer Of Marine Technology and Capaci...mentioning
confidence: 99%
“…On June 19, 2023, the Agreement under the United Nations Convention on the Law of the Sea on the conservation and sustainable use of marine biological diversity of areas beyond national jurisdiction (the BBNJ Agreement) was adopted in New York (BBNJ Agreement, 2023). As a significant addition to existing international ocean governance systems, once it has entered into force, this agreement will help improve integrated management of a changing ocean and support collaboration across regions and sectors to sustain marine ecosystems (Gjerde et al, 2022). In the context of legislative trends, the Agreement was successfully adopted in June 2022, which furthered ocean sustainability by prohibiting harmful fisheries subsidies that have contributed to the depletion of the world's fish stocks.…”
Section: Current Regulatory System For Iuu Fishing and Its Implicationsmentioning
confidence: 99%